Digital Public Sector: A Strategic Report - Beev, Ivaylo; Prodanov, Hristo (Research Papers, 2024)
The digital public sector differs significantly from the „classical“ public sector. Its virtual existence makes its association with real phenomena and processes particularly difficult, and with that, its theoretical understanding is also difficult. This necessitates a strategic view to understand the processes, shaping the still emerging digital public sector. For this purpose, through a descriptive, comparative, and rationalistic approach, a group of interrelated notions and the change as a result of digitalization in the relations between them are examined, which necessitates the need for a new understanding of what they actually mean in the new conditions.The publication presents part of the scientific results of the research project „Digital Public Sector“ (NID 21-2020, UNWE), also parts of various previous studies by the same authors.